Analisis Kendala dalam Pemungutan Pajak Alat Berat pada Bapenda Provinsi Jawa Barat UPTD Pusat Pengelolaan Pendapatan Daerah Wilayah Kabupaten Karawang - Imas Komalasari; Angga Sanita Putra; Nesti Hapsari; Kholida Atiyatul Maula; Achmad Nawawi (CV. ALIM'SPUBLISHING, 2026)
Heavy Equipment Tax is one of the provincial taxes implemented based on Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments. As a relatively new type of regional tax, its implementation still encounters various constraints that may affect the optimization of regional tax revenue. This study aims to identify the constraints in Heavy Equipment Tax collection, the factors causing such constraints, the efforts undertaken to overcome them, and the effectiveness of these efforts at BAPENDA of West Java Province, UPTD PPPD Karawang Regency Area. The study employed a descriptive method with a qualitative approach through observation, interviews, and documentation. The results of the study indicate that the main constraints in Heavy Equipment Tax collection include companies that have not reported the use of heavy equipment, the use of leased heavy equipment, and ownership of heavy equipment located outside the Karawang Regency area and the Province of West Java. The primary factor causing these constraints is that Heavy Equipment Tax is a relatively new type of tax, requiring further adjustments in its implementation. Efforts undertaken to address these constraints include field data collection, taxpayer outreach, and coordination with related agencies. These efforts have been relatively effective, as evidenced by the increase in the number of registered taxpayers and the realization of Heavy Equipment Tax revenue exceeding the established targets.